Dengue Virus Immunopathogenesis: Lessons Applicable to the Emergence of Zika Virus. Issue 17 (28th August 2016) - Olagnier, David; Amatore, Donatella; Castiello, Luciano; Ferrari, Matteo; Palermo, Enrico; Diamond, Michael S.; Palamara, Anna Teresa; Hiscott, John
Abstract: Dengue is the leading mosquito-transmitted viral infection in the world. There are more than 390 million new infections annually; while the majority of infected individuals are asymptomatic or develop a self-limited dengue fever, up to 1 million clinical cases develop severe manifestations, including dengue hemorrhagic fever and shock syndrome, resulting in 25, 000 deaths annually, mainly in children. Gaps in our understanding of the mechanisms that contribute to dengue infection and immunopathogenesis have hampered the development of vaccines and antiviral agents. Some of these limitations are highlighted by the explosive re-emergence of another arthropod-borne flavivirus—Zika virus—spread by the same vector, the Aedes aegypti mosquito, that also carries dengue, yellow fever and chikungunya viruses. This review will discuss the early virus–host interactions in dengue infection, with emphasis on the interrelationship between oxidative stress and innate immune pathways, and will provide insight as to how lessons learned from dengue research may expedite therapeutic strategies for Zika virus. Graphical abstract: Highlights: Dengue is the leading mosquito-transmitted viral infection in the world. Severe manifestations of dengue include plasma leakage and coagulation dysfunction. The arthropod-borne Zika virus has spread rapidly, with the complication of microcephaly in newborns. This review examines how dengue research may expedite therapeutic strategies for Zika virus.